Critical Practice Study of Nursing Evaluated by Teachers - Shearer, Jessica B; Lasonen, Johanna (International Journal for Research in Vocational Education and Training, 2018)
Purpose: Competent nursing care is essential to positive patient outcomes and quality patient care. Graduate nurses begin practice as novices in knowledge and experience often entering an environment where patients have several disease processes complicating their care. A strong foundation of educational competencies prior to entering practice is vital for the development and growth of graduate nurses into the role of RN. The purpose of this study was to examine the use of the Nurse Competence Scale among nursing faculty. Method: Nursing faculty were surveyed to determine which competencies were a priority in nursing practice. The Nurse Competence Scale was used to identify and categorize nurse competences. Brenner’s novice to expert theoretical framework was used to apply findings to curricular programs. IRB approval was granted from each educational institution. SPSS statistical analysis was used to analyze survey results. Results: Among the categories of the Nurse Competence Scale, nursing faculty identified Acting appropriately in life-threatening situations in the Managing Situations section as most important to practice. In the category of Helping, Planning patient care according to individual needs was identified as most important. Additionally the nursing faculty surveyed rated Contributing to further development of multidisciplinary clinical paths in the Therapeutic Interventions category as the lowest. Conclusion: This study contributes to the discussion on nursing competence. Priorities for nursing faculty aligned with register nurses in practice. This study helps pair nursing education with practice in several ways including aligning current practice with education. Nurse Educators may use these findings to help join curricular outcomes with practice. Evaluating each item on the Nurse Competence Scale using the critical to practice scale provides insight to the necessary skills and knowledge needed to be competent in nursing. In addition the results may be compared to current practice guidelines to ensure best practice. Further research linking education and practice using nursing competence is needed.